Modulation of Heat Shock Proteins Levels in Health and Disease: An Integrated Perspective in Diagnostics and Therapy - Elena Mikhailova; Alexandra Sokolenko; Stephanie E. Combs; Maxim Shevtsov (Cells)
Heat shock proteins belong to a highly conserved family of chaperone proteins, and in addition to their participation in the regulation of cellular proteostasis (folding of polypeptides and proteins, disaggregation of incorrectly folded peptides, and participation in autophagy processes), also play a significant immunomodulatory role in both innate and adaptive immunity. Changes in the HSP level, both downwards (e.g., in neurodegenerative diseases) and upwards (e.g., autoimmune, oncological diseases), underlie the pathogenesis of many somatic and oncological pathologies. In this review, we consider the main physiological mechanisms of HSP level regulation and also analyze pharmacological, genetically engineered methods of modulating the chaperone level, citing the advantages and disadvantages of a particular method of influence. In conclusion, modulation of the HSP level, according to numerous preclinical studies, can have a significant impact on the course of various pathological conditions, which, in turn, can be used to develop new therapeutic approaches, when the effect on the level of chaperones can be used as monotherapy or as an adjuvant method of action.